Investigating the effects of uncertainties in the upstream gas sector. (1st January 2013) - Eker, Sibel; van Daalen, Els
Natural gas is expected to become more important in the future to support the energy transition. However, the upstream gas sector faces many uncertainties which complicate the decision making to supply the required amounts of natural gas. This study deals with these uncertainties, by framing the natural gas production in a system of systems perspective, building a system dynamics model, carrying out an exploratory analysis and testing policy options. The results show that the annual production volume, energy consumption, onshore land use and CO2 emission objectives can be achieved in the Netherlands only in a small portion of the future scenarios. Policies such as production limits and end of field life techniques are beneficial to increase the production, but also increase CO2 emissions. In future studies, more policy alternatives can be generated and tested, the uncertainty analysis can be extended and the model can be used in broader energy models.